Where is the value in metadata?. (14th July 2008) - Lytras, Miltiadis D.; Sicilia, Miguel-Angel
Metadata can be defined as structured data about an object that supports some function(s) related to that object described. Thus, the functions enabled by metadata are the key to cost-justifying metadata creation and management efforts. However, the functions of metadata are diverse, and also the kinds of organisations that typically create and use metadata. This results in different possible accounts of the concept of 'metadata value'. This paper explores typical cases of organisations using metadata and then explores how metadata as an organisational asset can be framed in the existing Information Systems (IS) theories.